2018
DOI: 10.1007/s00259-018-4090-4
|View full text |Cite
|
Sign up to set email alerts
|

Serial FLT PET imaging to discriminate between true progression and pseudoprogression in patients with newly diagnosed glioblastoma: a long-term follow-up study

Abstract: PurposeResponse evaluation in patients with glioblastoma after chemoradiotherapy is challenging due to progressive, contrast-enhancing lesions on MRI that do not reflect true tumour progression. In this study, we prospectively evaluated the ability of the PET tracer 18F-fluorothymidine (FLT), a tracer reflecting proliferative activity, to discriminate between true progression and pseudoprogression in newly diagnosed glioblastoma patients treated with chemoradiotherapy.MethodsFLT PET and MRI scans were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…63,64 Although, single imaging studies have found feasible results, several studies have indicated that diagnosis of pseudo-progression could not be achieved by a single imaging technique and suggested that serial imaging will results in improved diagnosis accuracy. 65,66 On the other hand, there are several variations in the clinical definitions of pseudo-progression based on the imaging reports which require higher precision quantitative imaging. 67 Some radiomics studies have shown the feasibility of MR image radiomic features to discriminate between pseudo-progression compared to true progression [68][69][70] and genomic mutation prediction 8-11,71,72 and treatment response assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…63,64 Although, single imaging studies have found feasible results, several studies have indicated that diagnosis of pseudo-progression could not be achieved by a single imaging technique and suggested that serial imaging will results in improved diagnosis accuracy. 65,66 On the other hand, there are several variations in the clinical definitions of pseudo-progression based on the imaging reports which require higher precision quantitative imaging. 67 Some radiomics studies have shown the feasibility of MR image radiomic features to discriminate between pseudo-progression compared to true progression [68][69][70] and genomic mutation prediction 8-11,71,72 and treatment response assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment response evaluation in GBM suffers from several uncertainties in differentiation among pseudo‐progression, pseudo‐response, treatment‐related necrosis, and true progression 63,64 . Although, single imaging studies have found feasible results, several studies have indicated that diagnosis of pseudo‐progression could not be achieved by a single imaging technique and suggested that serial imaging will results in improved diagnosis accuracy 65,66 . On the other hand, there are several variations in the clinical definitions of pseudo‐progression based on the imaging reports which require higher precision quantitative imaging 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Other PET radiopharmaceuticals that are under investigation to differentiate between progression from pseudoprogression or tumor recurrence include 18 F-fluoromisonidazole (FMISO) PET/MR [48], 4-borono-2-[(18)F]-fluoro-phenylalanine ( 18 F-FBPA) PET [49], [(18)F]-fluoromethyl-dimethyl-2-hydroxyethylammonium ( 18 F-fluoromethylcholine) PET [50], and 3′-deoxy-3′-(18)F-fluorothymidine (FLT) PET [51].…”
Section: Diagnostic Imaging Modalitiesmentioning
confidence: 99%
“…[ 18 F]FLT has been extensively used in the field of oncology to characterize tumors and predict the response to personalized therapeutic approaches ( Schelhaas et al, 2017 ). Therefore, the main application of this radiotracer in neurology has been restricted to the diagnosis of glioblastoma ( Nikaki et al, 2017 ; Brahm et al, 2018 ). Nevertheless, few studies have reported the visualization of endogenous neural stem cells in living animals using [ 18 F]FLT after focal cerebral ischemia, that could be used to monitor the effect of drugs aimed at expanding the neural stem cell niche ( Rueger et al, 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%